PRINSIP, KARAKTERISTIK DAN MACAM-MACAM PROFESI HUKUM ERA DIGITALISASI - Bintang Raharja Pangestu; Rizka Amalia; Abdurrahman Abdurrahman; M. Muzakki (CV. KAMPUS AKADEMIK PUBLISING, 2024)
In this current era, digitalization of law is very much needed. In the digital era, more sophisticated technology will replace everything that is technological. Currently, artificial intelligence machines have a higher level of accuracy and legal certainty compared to the capabilities of the human legal profession. In the industrial revolution 4.0 phase, digital advances are changing the paradigm and way people practice law, people do not need to consult a law office, because artificial intelligence machines provide answers to various legal problems. In fact, law firms, courts, police and prosecutors will also increasingly depend on artificial intelligence machines.The performance of artificial intelligence machines has been proven to be faster and more accurate than human legal professions in identifying and analyzing legal problems. Of course, that doesn't mean it can immediately replace all the roles of the human legal profession. Intelligence machines are limited to providing legal certainty, while in certain legal cases there is a struggle between certainty, expediency and justice. Justice is not a matter of algorithms, but rather of conscience, sensitivity to human values, and a critical perspective on reality. Strictly speaking, to bring the law closer to justice, the legal profession requires human beings who have integrity and have an intelligent conscience.